A left lateral body position increases pulmonary vein stress in healthy humans. Issue 18 (23rd September 2021) - Gottlieb, Lisa A.; El Hamrani, Dounia; Naulin, Jérôme; Sanchez Y. Blanco, Lorena; Lamy, Jérôme; Kachenoura, Nadjia; Quesson, Bruno; Cochet, Hubert; Coronel, Ruben; Dekker, Lukas RC
Abstract: Pulmonary vein (PV) stretch is proarrhythmic for atrial fibrillation (AF). AF patients often report that a left lateral (LL) body position can trigger arrhythmia symptoms. Because the PV myocardium is thought to trigger AF, we hypothesized that the LL compared to the supine body position increases PV wall stress. Functional cardiac magnetic resonance imaging was performed in supine and LL recumbent body position in awake condition in healthy human volunteers ( n = 20). Following a change from supine to LL position, the heart moved in an anterior‐LL direction in the thorax. The right superior PV diameter was increased by 19% (24.6 ± 3.1 vs. 20.7 ± 3.2 mm, p = 0.009) and left atrial (LA) volume was larger by 17% (61.7[15.4] vs. 51.0[17.8] ml, p = 0.015) in LL than supine position, respectively. The passive LA conduit fraction (normalized difference between maximum and pre‐contraction LA volume) increased by 25% in LL compared to supine position (19.6 ± 9.0 vs. 15.7 ± 7.6%, respectively, p = 0.016). Local wall stress in the PV regions increased in LL compared to supine position (overall mean: 1.01 ± 0.12 vs. 1.10 ± 0.10 arb. unit, LL vs. supine, position effect p = 0.041), whereas this was not the case in the LA walls (overall mean: 1.18 ± 0.31 vs. 1.21 ± 0.21 arb. unit, LL vs. supine, position effect p = 0.381). In conclusion, a left lateral body position increases PV myocardial stress during the atrial relaxation phase of healthy volunteers. These results have implications for the mechanisms of posture‐triggered AF. Abstract : Atrial fibrillation can be triggered by taking a left lateral recumbent position. We show that a left lateral position causes anterior‐left localization of the heart and increases stress in the pulmonary veins.